Synthesis and Characterization of Novel Ni(II), Cu(II) and Cd(II) Complexes of 4-(2-Chlorphenylazo)-1H-pyrazole-3,5-diamine - Adiguzel, Ragip; Esener, Hasan; Ergin, Zuhal; Aktan, Ebru; Sekerci, Memet (Asian Journal of Chemistry, 2011)
In this study, the diazotized o-chloraniline was coupled with malononitrile. The ring closure reaction of the obtained product with hydrazine monohydrate yielded 4-(2-chlorophenylazo)-1H-pyrazole-3,5-diamine (L). The structure of ligand has been elucidated by spectroscopic analyses. Then, novel Ni(II), Cu(II), Cd(II) complexes of ligand have been synthesized and the structures of these complexes determined by elemental analysis, spectrometric and TGA/DTA methods and magnetic susceptibility measurements. All complexes were monomeric and diamagnetic. From the elemental analyses and mass spectra data, the complexes were proposed to the formulae [Ni2L2(Cl)(2)]center dot 2Cl center dot 0.5DMF center dot 0.5H(2)O(2), [Cu3L2(Cl)(4)(OH)(2)(H2O)(2)]center dot 0.5H(2)O and [Cd3L2(Cl)(2)(OH)(2)](Cl)(2)center dot 1.5H(2)O. For the Ni(II) complex square planar and for the Cu(II) complex octahedral geometry were proposed, but the Cd(II) complex includes both four and six coordinated structures. The Cu(II) and the Cd(II) complexes were found to be trinuclear. On the other hand the Ni(II) complex was found to be dinuclear.
Keywords: 4-(2-Chlorphenylazo)-1H-pyrazole-3,5-diamine and metal complexes; Azodyes complexes